Análise da relação da radiação solar na formação de ilhas de calor em diferentes configurações urbanas em Cuiabá – MT - Souza, Natallia Sanches e (2016)
The change in built space compromises severely the natural resources and has reflected directly in changing the local climate. The modification of the natural environment to an urban environment results in phenomena such as urban heat island, which is characterized by a higher air temperature in urban environment, when compared to neighboring regions less urbanized. In order to produce a balanced urban ambience with the environment and suitable for human needs must be considered a close relationship of the urban environment with the microclimate. The climate of Cuiabá is Aw in the Koppen classification with high temperatures, rain in summer and dry in winter. Exposed this, this study aimed to analyze the relationship of solar radiation in the formation of heat islands in different urban settings in Cuiabá. For this we used three micrometeorological stations of Onset brand for analyses meteorological variables (air temperature, relative humidity and solar radiation) during the period from August/2014 to July/2015 in different land cover in Cuiabá. Based on the results, there was the formation of heat islands in two urban portions, which has dense urbanization, while the portion with higher vegetative and water index presented the formation of cool island. Urban portions that showed urban heat island has their peak in the morning, between 8 am and 10 am. So the occupation of the urban environment, as the materials contained in it, influence the microclimate of the region and the formation of thermal anomalies as heat islands. Hoped that with the results of this research, the urban climate studies for the Mato Grosso state be enriched, noting the importance of analyzing the land cover in urban planning in order to mitigate climate rigor imposed by the climate of developing cities, such as Cuiabá.